Antithrombotic properties of policosanol rice (Oryza sativa L.) bran in modulating blood platelet properties in in vitro, ex-vivo and in vivo model - Wong, Wai Teng (2020)
In recent decades, sugarcane policosanol was shown to be effective in preventing platelet aggregation by Cuban researchers. However, there were some identifiable gaps in the research in which the underlying mechanisms details were lacking. The policosanol content was not quantified and its impact on other important related markers was not assessed. Moreover, the anti-platelet effect of policosanol from other plant sources was never been investigated. The general objective of this research project was to investigate the anti-platelet functions of rice bran policosanol extract. The project started with policosanol extraction and sonication using hexane and methanol (20:1 v/v) was the best method yielded 877.99±110.11mg policosanol/100g extract. Gas chromatography mass spectrometer (GCMS) analysis showed that tetracosanol was the dominant component (371.80±45.27mg/100g extract). On the other hand, in vitro antioxidant analysis showed that policosanol had strong antioxidant power, with EC50=8.53mg/mL and EC50=10.55mg/mL respectively in both 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay and beta carotene bleaching (BCB) assay. The project was then continued with in vitro study using microtiter method and 500μg/mL policosanol extract was shown to inhibit adenosine diphosphate (ADP)-induced platelet aggregation up to 52.79±5.95%. The research project was further extended to ex vivo and in vivo analysis using high fat diet fed male Sprawgue Dawley rats. The results obtained revealed that 250mg/kg policosanol treatment exerted highest platelet aggregation inhibitory effect which was up to 53% . Besides, 500mg/kg policosanol treatment inhibited lipid peroxidation by 33%. On the other hand, policosanol extract did not prolong both bleeding time (521.2±97.16 secs) and coagulation time. In addition, policosanol extract was shown to modulate platelet glycoproteins and soluble biomarkers expression positively while regulating lipid profile without exerting harmful effects as revealed by in vitro and in vivo toxicity analysis. With all the solid findings, rice bran policosanol was suggested to be a good anti-platelet candidate in arterial thrombosis prevention.